Persistent pulmonary hypertension in a neonate with Vein of Galen malformation: Vein of Galen malformation associated pulmonary hypertension - Vasic, Karin; Vucic, Jelena; Mutlag, Misel (Medicinski časopis, 2025)
The vein of Galen malformation (VGAM) is a rare congenital vascular malformation. However, in 40-50% of cases, it can present in the newborn period as high-output congestive heart failure and rarely as neonatal persistent pulmonary hypertension (PPHN). We present the case of a female neonate born at 31 weeks’ gestation via urgent cesarean section. As the newborn was premature with signs of respiratory distress, it was admitted to our hospital’s neonatal intensive care in the 14th hour of life. On the 8th day of life, a cardiac murmur was noted, and a cardiology consultation was obtained. Echocardiography was performed to exclude critical congenital heart disease, but rather showed existing persistent pulmonary hypertension of the newborn (PPHN) with near systemic pulmonary pressures. The patient was started on sildenafil and a low-dose diuretic. Initially, there was an overall improvement in the child’s general condition. However, the patient deteriorated on 15th day of life. Repeat echocardiography revealed suprasystemic PPHN, with global ventricular dysfunction, and ductal flow reversal was noted at the level of the aortic isthmus and right-to-left shunting at the atrial level. Anticongestive medications (ACE inhibitor, diuretics) were given in addition to sildenafil. Cranial ultrasound was ordered, and the scan revealed a midline cystic formation measuring 13.7 x 13.2 mm with color Doppler showing turbulent blood flow in the vein of Galen area, which was diagnostic for vein of Galen malformation. Treatment of our patient included mechanical ventilation and other supportive measures, treatment of congestive heart failure, and PPHN. However, the neonate remained in critical condition, and even though endovascular embolization was considered, transfer to a neurosurgical center was impossible, and the baby succumbed to her disease. Even though the association of VGAM with PPHN of the newborn is not common, in cases of systemic PPHN and congestive heart failure refractory to treatment, AV malformations in the liver and brain should be ruled out.